Sacrococcygeal sinus angle: as a new anatomic landmark for the posterior approach of presacral lesions - Kaplan, Metin; Ozturk, Sait; Cakin, Hakan; Akgun, Bekir; Onur, Mehmet Ruhi; Erol, Fatih Serhat (Springer, 2014)
We have discussed the importance of sacrococcygeal sinus angle (SSA), which is a new anatomical landmark in the surgery of presacral lesions. Because of its anatomical structure, the sacrum limits the surgical exposure like a compact barrier for the posterior surgical approach. The main aim of this paper is to explain the anatomical description and clinical importance of SSA in the surgery of presacral lesions. Three groups were designated, consisting of ten patients in each group, as early childhood (group 1), late childhood (group 2) and adulthood (group 3). Patients were selected randomly. The degree of SSA measurement was performed between the line tangent to the anterior margin of the first sacral vertebra and the line from the promontorium to the tip of the coccyx. The measurement of SSA was performed on patients' lumbosacral magnetic resonance images. When the SSA forms a triangle via a parallel line starting from the inferior tip of the sacrum and running parallel to the ground, the area of the triangle also covers the field of view of the presacral region. In addition, the sacral region needed to be resected for maximum exposure is also within this area. The mean SSA was measured to be 53.9 +/- A 11.4A degrees in group 1, 77.8 +/- A 11.2A degrees in group 2 and 74.5 +/- A 12.5A degrees in group 3. Intergroup comparisons revealed a significant difference between group 1 and the other two groups statistically. It was found that the SSA was 20A degrees less in group 1 as compared to the other age groups (p = 0.0005). The area of a triangle is calculated using the sine area formula, and according to this formula the area of a triangle increases when the degree of the angle increases, thus comprising larger part of the sacrum. This condition requires more and wide sacral resection to obtain maximum exposure in the presacral zone. We have observed that the SSA is significantly smaller during early childhood compared with the other age groups. This feature provides an anatomical superiority in this age group for the posterior approach in the surgical treatment of presacral masses.
Keywords: Coccyx; Presacral lesions; Sacrococcygeal sinus angle; Sacrum